Variations in the Gut Microbiota in Breast Cancer Occurrence and Bone Metastasis - Wenhui, Yu; Zhongyu, Xie; Kai, Chen; Zhaopeng, Cai; Jinteng, Li; Mengjun, Ma; Zepeng, Su; Yunshu, Che; Peng, Wang; Yanfeng, Wu; Huiyong, Shen (Frontiers in Microbiology, 2022)
Breast cancer is the most common cancer in women and the second most common cancer overall. Although advancements in the early diagnosis and therapy of breast cancer have occurred in recent years, the prognosis of breast cancer bone metastasis remains poor and this type of cancer is rarely cured. The gut microbiota is indispensable for internal homeostasis and regulates various biological processes. Understanding the gut microbiota profiles in normal controls (NCs), breast cancer patients with no metastasis (BNs), and breast cancer patients with bone metastasis (BMs) may shed light on the development of diagnostic and therapeutic targets for breast cancer and bone metastasis. We comprehensively analyzed the gut microbiota from NCs, BNs, and BMs and found that the community diversity decreased in the order of NCs, BNs, and BMs. Streptococcus, Campylobacter and Moraxellaceae showed higher abundances in BNs and BMs than in NCs. The lack of Megamonas and Akkermansia in the BM compared with those in the NC and BN groups was considered related to bone metastasis. Additionally, based on the distinct gut microbiota profiles, we predicted that lipid transportation and metabolism, as well as folate biosynthesis, participate in breast cancer occurrence and that steroid hormone biosynthesis influences bone metastasis. Our study demonstrated that variations in gut microbiota are associated with breast cancer occurrence and bone metastasis, providing attractive targets to develop therapeutic and diagnostic methods.